1994
DOI: 10.1128/mcb.14.3.1845
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous interleukin 1 alpha must be transported to the nucleus to exert its activity in human endothelial cells.

Abstract: We have previously shown that the signal peptideless cytokine interleukin 1a (IL-la) may play a role as an intracellular regulator of human endothelial cell senescence (J. A. M. Maier, P. Voulalas, D. Roeder, and T. Maciag, Science 249: [1570][1571][1572][1573][1574] 1990). To investigate the potential intracellular function of IL-lot, transformed endothelial cells were transfected with the human cDNAs that code for the two forms of IL-la, the precursor molecule IL-11-27, and the mature protein IL-11.3-271* Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 49 publications
(38 reference statements)
4
90
0
Order By: Relevance
“…As an intracellular molecule, IL-1␣ has been also shown to be inserted in the membrane and act in a juxtacrine manner (3,4,23). However, there is growing evidence for intracellular functions of IL-1␣, including promotion of senesence (12), cell growth and differentiation (7) and regulation of gene expression (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an intracellular molecule, IL-1␣ has been also shown to be inserted in the membrane and act in a juxtacrine manner (3,4,23). However, there is growing evidence for intracellular functions of IL-1␣, including promotion of senesence (12), cell growth and differentiation (7) and regulation of gene expression (24).…”
Section: Discussionmentioning
confidence: 99%
“…pIL-1␣ possesses a KVLKKRR nuclear localization site in its N-terminal propiece (6). In fact, pIL-1␣ translocates to the nucleus in a variety of cells, and this appears to be necessary for specific downstream events (7). pIL-1␣ is found in keratinocytes and epithelial cells of healthy subjects, and mice deficient in IL-1␣ do not exhibit an apparent phenotype (8) unless challenged by disease processes, suggesting that a putative function for the intracellular pIL-1␣ requires an additional external stimulus.…”
mentioning
confidence: 99%
“…However, PD45 cells cultured with VPF/VEGF continuously after PD26 and then withdrawn from VPF/VEGF for 7 days incorporated signi®cantly less thymidine than PD47 cells cultured continuously with VPF/VEGF (P50.001) therefore, the p53 expressed in senescent cells and VPF/VEGF-treated cells could be functionally different, a possibility that requires further investigation. Maier et al (1994) suggested that endogenous IL-1a is critical in the progression of human umbilical vein endothelial cells toward senescence. However, we did not detect any signi®cant di erences in IL-1a expression between young, senescent and VPF/VEGF-treated HDMEC (data not shown).…”
Section: Altered Gene Expression In Senescent Hdmecmentioning
confidence: 99%
“…IL1ra binds interleukin-1 receptor 1 (IL1R1), and prevents IL1b mediated signal transduction. 18 Even at 1,000 fold molar excess, IL1ra had no effect on the growth of MCF10A-C/EBPb2 cells, either in the presence or absence of EGF (Fig. 2F).…”
Section: Genomic Profiling Of C/ebpb2 Transformed Mammary Epithelial mentioning
confidence: 99%